Sagot :
Answer:
D
Step-by-step explanation:
How to solve your problem
Topics: Algebra, Quadratic Equation
2
−
5
+
6
=
0
x^{2}-5x+6=0
x2−5x+6=0
Quadratic formula
Factor
1
Use the quadratic formula
=
−
±
2
−
4
√
2
x=\frac{-{\color{#e8710a}{b}} \pm \sqrt{{\color{#e8710a}{b}}^{2}-4{\color{#c92786}{a}}{\color{#129eaf}{c}}}}{2{\color{#c92786}{a}}}
x=2a−b±b2−4ac
Once in standard form, identify a, b and c from the original equation and plug them into the quadratic formula.
2
−
5
+
6
=
0
x^{2}-5x+6=0
x2−5x+6=0
=
1
a={\color{#c92786}{1}}
a=1
=
−
5
b={\color{#e8710a}{-5}}
b=−5
=
6
c={\color{#129eaf}{6}}
c=6
=
−
(
−
5
)
±
(
−
5
)
2
−
4
⋅
1
⋅
6
√
2
⋅
1
x=\frac{-({\color{#e8710a}{-5}}) \pm \sqrt{({\color{#e8710a}{-5}})^{2}-4 \cdot {\color{#c92786}{1}} \cdot {\color{#129eaf}{6}}}}{2 \cdot {\color{#c92786}{1}}}
x=2⋅1−(−5)±(−5)2−4⋅1⋅6
2
Simplify
Evaluate the exponent
Multiply the numbers
Subtract the numbers
Evaluate the square root
Multiply the numbers
=
5
±
1
2
x=\frac{5 \pm 1}{2}
x=25±1
3
Separate the equations
To solve for the unknown variable, separate into two equations: one with a plus and the other with a minus.
=
5
+
1
2
x=\frac{5+1}{2}
x=25+1
=
5
−
1
2
x=\frac{5-1}{2}
x=25−1
4
Solve
Rearrange and isolate the variable to find each solution
=
3
x=3
x=3
=
2
x=2
x=2
Solution
=
3
=
2